(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This research investigated the intersections between body, technology and magic in some theoretical studies of the performing arts, using the biotechnomagical regime as a methodology for creation in art and education. By expanding studies of the body and pedagogies of movement, it aimed to systematize artistic-pedagogical aspects that interact with contemporary and ancestral technologies. The investigation, with a qualitative and performative approach, intertwined concepts about a biotechnological and ancestral body as an expanded locus for the scene, starting from assumptions inherent to the biotechnomagical regime to expand the potential for creation in art and education.